Citrus flavonoids for overcoming breast cancer resistance to methotrexate: identification of potential targets of nobiletin and sinensetin - Adam Hermawan; Naufa Hanif; Dyaningtyas Dewi Pamungkas Putri; Nurul Fatimah; Heri Himawan Prasetio (Discover Oncology)
Abstract Breast cancer is a potentially fatal illness that affects millions of women worldwide. Methotrexate (MTX) may be beneficial for treating breast cancer; however, high doses and prolonged use can cause drug resistance. Although certain citrus flavonoids—nobiletin, sinensetin, tangeretin, hesperidin, hesperetin, and naringenin—may overcome resistance to chemotherapy, no study has investigated MTX resistance. This study investigated the potential of natural chemicals, specifically nobiletin and sinensetin, to overcome MTX resistance in breast cancer cells using MTX-resistant MCF-7 (MCF-7/MTX) and MCF-7 cells. Protein targets of citrus flavonoids were identified from multiple databases and were collected using Venny 2.1. Microarray data of MCF-7 and MCF-7/MTX cells were acquired from the Gene Expression Omnibus. Subsequently, we constructed a protein–protein interaction network and selected the hub proteins. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis, drug– and disease–gene enrichment analyses, genetic alteration examination, receiver operating characteristic curve analysis, mRNA levels analysis, prognostic value analysis, and molecular docking analysis were performed along with in vitro experiments. Cytotoxicity of citrus flavonoids (individually and combined) was assessed in MCF-7/MTX cells. Nobiletin and sinensetin significantly enhanced the cytotoxicity of MTX in MCF-7/MTX cells. BCL2L1, CDK1, EGFR, PTGS2, PLK1, MMP2, ACHE, ABCG2, and KIT genes were enriched in cholinesterase activity, cell cycle regulation, and the PI3K/Akt signaling pathway. Nobiletin and sinensetin impeded PLK1, CDK1, and ACHE activities based on molecular docking. Nobiletin and sinensetin in combination with MTX may overcome breast cancer cell resistance to MTX.